Chemometric Analysis of essential oils from Tunisian Plants: Unravelling the Antifungal Potential against Botrytis cinerea - Safa Rguez; Taycir Grati-Affes; Walid Yeddes; Majdi Hammami; Ibtissem Hamrouni-Sellami (Tunisian Journal of Plant Protection)
Rguez, S., Grati-Affes, T., Yeddes, W., Hammami, M., and Hamrouni-Sellami, I. 2024. Chemometric analysis of essential oils from Tunisian plants: Unravelling the antifungal potential against Botrytis cinerea. Tunisian Journal of Plant Protection 19 (1): 13-26.